2014
DOI: 10.1097/aln.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cognitive Aid on Adherence to Perioperative Assessment and Management Guidelines for the Cardiac Evaluation of Noncardiac Surgical Patients

Abstract: BACKGROUND The 2007 American College of Cardiologists/American Heart Association Guidelines on Perioperative Cardiac Evaluation and Care for Noncardiac Surgery is the standard for perioperative cardiac evaluation. Recent work has shown residents and anesthesiologists do not apply these guidelines when tested. This research hypothesized that a decision support tool would improve adherence to this consensus guideline. METHODS Anesthesiology residents at 4 training programs participated in an unblinded prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…However, only a handful of randomised trials that address smartphone applications with educational purposes are available in the literature. Most of them have been conducted among postgraduate students undergoing specialty training, and used smartphones as cognitive aids concomitant to assessments of very specific competences [ 10 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a handful of randomised trials that address smartphone applications with educational purposes are available in the literature. Most of them have been conducted among postgraduate students undergoing specialty training, and used smartphones as cognitive aids concomitant to assessments of very specific competences [ 10 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes A 40-item multiple-choice test was developed to measure the knowledge benchmark (pretest), acquisition (posttest), and retention (4-month retention test). Design and assessment of test questions involved a modified Delphi technique, 12,13 with question writing and review by 6 expert anesthesiologist educators to promote content validity. 14 Questions were piloted with 26 PGY-2 residents who did not participate in the study.…”
Section: Residents Received a Retention Test 4 Months After The Intermentioning
confidence: 99%
“…Our experience supports the use of mobile devices and apps to disseminate cognitive aids around the world. Cognitive aids based on national medical society guidelines are continuing to gain widespread acceptance in healthcare . Investigators have demonstrated that group performance during critical event management is better when groups have access to a cognitive aid compared to groups without such assistance .…”
Section: Discussionmentioning
confidence: 99%